2015
DOI: 10.1186/s12868-015-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking a vicious cycle nNOS/peroxynitrite/AMPK by S-nitrosoglutathione: implication for stroke therapy

Abstract: BackgroundStroke immediately sets into motion sustained excitotoxicity and calcium dysregulation, causing aberrant activity in neuronal nitric oxide synthase (nNOS) and an imbalance in the levels of nitric oxide (NO). Drugs targeting nNOS-originated toxicity may therefore reduce stroke-induced damage. Recently, we observed that a redox-modulating agent of the NO metabolome, S-nitrosoglutathione (GSNO), confers neurovascular protection by reducing the levels of peroxynitrite, a product of aberrant NOS activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
(99 reference statements)
1
34
0
Order By: Relevance
“…Taken together, these observations indicate a disturbed NO metabolome in TBI. This disturbed NO metabolome in TBI is supported by previous studies from our laboratory in TBI (Khan et al, 2011) and stroke (Khan et al, 2012; Khan et al, 2015b) and the current results, which show increased enzymatic nNOS activity (Fig 1B) and sustained high levels of peroxynitrite for a prolonged periods (Figs 2D–d and 4B–b). We investigated the mechanisms of the efficacy of GSNO for TBI therapy because it corrected not only the disturbed NO metabolome (Fig 1) and NO/S-nitrosylation-based cellular functions (Khan et al, 2005; Khan et al, 2011; Khan et al, 2015a; Sakakima et al, 2012) but also provided neuroprotection and improved neurological functions, as shown in Fig 5.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Taken together, these observations indicate a disturbed NO metabolome in TBI. This disturbed NO metabolome in TBI is supported by previous studies from our laboratory in TBI (Khan et al, 2011) and stroke (Khan et al, 2012; Khan et al, 2015b) and the current results, which show increased enzymatic nNOS activity (Fig 1B) and sustained high levels of peroxynitrite for a prolonged periods (Figs 2D–d and 4B–b). We investigated the mechanisms of the efficacy of GSNO for TBI therapy because it corrected not only the disturbed NO metabolome (Fig 1) and NO/S-nitrosylation-based cellular functions (Khan et al, 2005; Khan et al, 2011; Khan et al, 2015a; Sakakima et al, 2012) but also provided neuroprotection and improved neurological functions, as shown in Fig 5.…”
Section: Discussionsupporting
confidence: 90%
“…In this cell free system, a treatment with SIN-1, a peroxynitrite-producing agent (Khan et al, 2006; Pacher et al, 2007), significantly and dose dependently increased whereas GSNO significantly and dose dependently decreased calpain activity (Fig 3A). Reversal of the SIN-1-mediated enhanced calpain activity by FeTPPS, a peroxynitrite scavenger (Khan et al, 2015b; Thiyagarajan et al, 2004), supports the role of peroxynitrite for increasing calpain activity, likely via the mechanism of 3-nitrotyrosination (Fig 3B). Blocking the GSNO-mediated reduced calpain activity by HgCl 2 , a Cys-NO bond cleaving agent (Cook et al, 1996), supports the role of GSNO in decreasing calpain activity, likely via the mechanisms of S-nitrosylation (Fig 3B).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These data support the hypothesis that AMPK activation in the acute phase of stroke is associated with injury. 108 To corroborate the idea that AMPK activation is harmful in ischemic stroke, preclinical studies demonstrated that mice deficient in AMPKα2 have less injury and show a reduced total infarct volume compared with wild-type littermates in an MCAO reperfusion model. AMPKα1-knockout mice have no difference in injury compared with wild-type mice, suggesting that AMPKα2 isoform plays a more significant role in the damaging response of AMPK activation in ischemic brain.…”
Section: Ampk Regulation In Strokementioning
confidence: 98%